ANALISIS PANDANGAN PEGAWAI YAYASAN PENDIDIKAN RUMAH QURAN ELFAJR TERHADAP FENOMENA SANDWICH GENERATION DITINJAU DARI HUKUM EKONOMI ISLAM (Muamalah, 2022)
The term sandwich generation in the literature has been widely heard in economic terms since 1981, where it is meant that the term sandwich generation is the generation in which he supports himself, his wife and children, but at the same time supports his parents or in-laws. The situation at the same time is what makes this term arise, where economists say this is not good for one's economy, where the sandwich generation pattern is considered a burden in one's economy. The purpose of this study is to find out how the views of employees of the El Fajr Quran house education foundation on the phenomenon of sandwich generation in terms of Islamic economic law. This research is a qualitative research with a qualitative descriptive approach using a structure interview as a research technique. . This study resulted in a type of understanding of the sandwich generation phenomenon among employees of the Elfajr Quran House Foundation in terms of Islamic economic law. Keywords: Sandwich generation, sandwich generation, economic law.